Cross-modality Accuracy of Dual-step, Prospectively Electrocardiography-triggered Dual-source Computed Tomorgaphy Compared With Same-day Echocardiography and Cardiac Magnetic Resonance Imaging in the Follow-up of Heart-transplant Patients. Issue 4 (July 2018) - Marano, Riccardo; Merlino, Biagio; Natale, Luigi; Savino, Giancarlo; Vingiani, Vincenzo; Rovere, Giuseppe; Larici, Anna Rita; Iezzi, Roberto; Magarelli, Nicola; Lombardo, Antonella; Pasquale, Massimo; Manfredi, Riccardo
Abstract : Purpose: An accurate evaluation of left ventricular volumes, mass, and ejection fraction (EF) and an early exclusion or detection of significant coronary artery disease or cardiac allograft vasculopathy are mandatory for clinical management and prognosis assessment of heart-transplanted patients (HTP). The purpose of this article was to evaluate the role of dual-step prospective electrocardiography-triggered Dual-Source CT (pECGdual-step -DSCT) in HTP for the assessment of left-ventricular function, in comparison with echocardiography (echo) and cardiac magnetic resonance (CMR) performed on the same day, and of the coronary arteries as well. Materials and Methods: Left-ventricular EF, end-diastolic volume, end-systolic volume, stroke volume, cardiac output (CO), and mass were assessed in 11 HTP by pECGdual-step -DSCT in comparison with CMR and echo performed on the same day. During all the examinations, the heart rate was recorded. CT coronary artery assessment was also performed. Results: Heart rate was lower during DSCT (75.6±7.8 bpm; P <0.001). EF resulted slightly lower for DSCT (55.7%±5.0%; P ≥0.05) in comparison with CMR (57.8%±5.3%; P ≥0.05) and echo (59.2%±5.6%; P ≥0.05). DSCT showed statistically significant higher end-diastolic volume (153.7±24.2 mL), end-systolic volume (67.8±11.5 mL), and stroke volume (85.9±17.6 mL) ( P <0.01 up to 0.001) than CMR, but with a high correlation ( P <0.001). Cardiac output was almost similar for DSCT versus CMR, with a very high correlation coefficient ( r =0.914; P <0.001). DSCT showed higher mass values than CMR ( P <0.001), but with a high correlation ( r =0.866; P <0.001). DSCT versus echo results were less correlated. No significant coronary artery disease was detected. Conclusion: pECGdual-step -DSCT allows reliable assessment of left-ventricular function in HTP, with good agreement and correlation with CMR, within a global diagnostic approach including coronary artery evaluation in one single-volume acquisition.